Barriers to Using Effective Teaching Strategies by English Teachers at Primary Level for Language Learning Engagement - Ihsan Ur Rahman,; Muhammad Waris,; Salman Ahmad, (Development in Language Studies, 2025)
Language learning is based on provision of effective guidance for enhancing student learning engagement. This research aimed to examine barriers to using effective instructional approaches by teachers in English lessons at the primary level in UC Kamala District Lower Dir. The research described in this paper applies descriptive methods. The research was conducted in nine major primary schools within UC Kamala Tehsil Adenzai. Data were collected through questionnaire from teachers selected according to their seniority qualifications and teaching experience. The analysis of the data showed that the schools practiced student engagement practices. The teachers were properly trained. However, outdated instructional methods dominated the teaching practices while teachers failed to develop listening and speaking abilities among their students. The study showed the problems of student engagement mostly arose from teachers' non-participation in training sessions, insufficient educational tools, and low quality of educational materials. The researcher recommends that government support should focus on offering refresher classes and audio-visual educational resources to schools. Different communicative classroom activities combined with appropriate motivational approaches from the teacher will assist student learning engagement.